Deskripsi Model Mental Peserta Didik pada Sub Topik Faktor-Faktor yang Mempengaruhi Laju Reaksi di Kelas XI SMAN 12 Padang - Dede Dwika Firmansah; Dwi Finna Syolendra (Lembaga Yasin AlSys, 2026)
Although understanding the concept of reaction rate in chemistry learning does not depend only on memorization ability but also on students’ mental models in connecting macroscopic, submicroscopic, and symbolic representations, students still often experience difficulty in comprehensively understanding the factors that affect reaction rates. This study aims to describe students’ mental models regarding the factors that affect reaction rates. This study used a qualitative method involving 30 eleventh-grade students of SMAN 12 Padang as research subjects. Data were collected using an essay test instrument covering two main topics, namely the concept of the factors that affect reaction rates, including concentration, surface area, temperature, and catalysts, as well as the application of these concepts in the form of curves and images. The data were analyzed by categorizing students’ answers into three mental model categories, namely initial (I), synthetic (ST), and scientific (SC) mental models. The results showed that students were better able to explain concepts at the macroscopic representation level than at the submicroscopic and symbolic levels. Students’ mental models regarding the factors that affect reaction rates were dominated by initial mental models at 48%, followed by scientific mental models at 28% and synthetic mental models at 24%. In addition, the relationship between chemical representations and students’ mental model categories showed a pattern that was almost aligned with the characteristics of the chemical representations possessed by the students. These findings confirm that mental model analysis is important for identifying students’ level of conceptual understanding and potential misconceptions in learning reaction rates. The implications of this study contribute to the development of chemistry learning strategies that place greater emphasis on the integration of macroscopic, submicroscopic, and symbolic representations.